Local Food-Based Mediterranean-Style Nutrition Education Improves Dietary Adherence, Sleep Quality, and Psychological Wellbeing Among Third-Trimester Pregnant Women - Dwi Rahmawati; Wahyu Indah Dewi Aurora; Liani Styarsih; Andika Sulistiawan (Al Jahiz, 2026)
Maternal nutrition is shaped by cultural food knowledge and local biodiversity, yet these factors are rarely integrated into dietary interventions for pregnant women. This study aimed to evaluate the effects of a local food–based Mediterranean-style nutrition education program on dietary adherence, sleep quality, and psychological wellbeing among third-trimester pregnant women, and to examine the association between ethnobiological literacy and dietary adherence. A quasi-experimental pretest–posttest design was conducted in Jambi City, Indonesia, involving 168 participants (84 intervention; 84 control) selected through accidental sampling. The intervention group received locally adapted Mediterranean-style nutrition education for 30 days, while the control group received standard antenatal nutrition counseling. Results showed significant improvements in the intervention group, including increased Mediterranean Diet Adherence Screener (MEDAS) scores (6.1 ± 1.4 to 9.2 ± 1.6; p < 0.001), improved sleep quality indicated by lower Pittsburgh Sleep Quality Index (PSQI) scores (7.8 ± 2.1 to 5.1 ± 1.8; p < 0.001), and higher psychological wellbeing measured using the WHO-5 Well-Being Index (46.7 ± 8.9 to 58.3 ± 9.7; p < 0.001). The control group showed minimal and non-significant changes. These findings suggest that nutrition education integrating local food resources with Mediterranean-style dietary principles can improve maternal dietary behavior and wellbeing.